Shear Behaviour of Ligthweight Sandwich Reinforced Concrete Slabs - Wahyuni, Ade; Vimonsatit, Vanissorn; Nikraz, Hamid (Multi-Science Publishing Co Ltd, 2012)
A new lightweight sandwich reinforced concrete (LSRC) section has been developed using prefabricated autoclaved aerated concrete (AAC) blocks as infill in the section where concrete is considered ineffective under bending. This paper presents an investigation into the strength and behaviour of LSRC slabs subjected to shear. Eight tests were conducted on four slabs, one solid and three different types of LSRC slabs. Based on the test results, all LSRC slabs exhibited similar behaviour to the equivalent solid slab and had varying shear capacities depending on the profile of AAC blocks infill. The obtained shear capacities were compared with the design values based on several major design codes and found to be within the safety predictions of the codes. ANSYS was employed to develop nonlinear finite element models of LSRC slabs. The numerical results agree well with the experimental one.